Investigation of Whether Target Capital Structure Exists in UK Companies - GE, Zhenrong (2011)
Empirical investigation has uncovered some facts about capital structure in the USA; very little research based upon firms in UK. Using a partial adjustment model and panel methodology for a sample of 20 UK firms during 1990 -2010, this paper shed new light on: (i) identify a target capital structure; (ii) investigate evidence of adjustment towards the target; and (iii) identify the determinants of capital structure in the target capital structure model.